Grupos econômicos de fato e a responsabilidade tributária ante a omissão legislativa. - Gomes, Igor Tenório (2019)
Tax liability has become one of the most important objects of study within the tax law makers and lawyers, because of its controversies and practical applications. Today, academic debates are questioning the possibilities of liability attribution of taxation because of the participation in economic groups. The absence of legislation summed up with the judicial empowerment, raised the debates regarding legal certainty. The problem that this project faces is: Is there any possibility for the tax liability for third parties because of their participation in economic groups? The hypothesis is that there is no legislation regarding the subject, and the judicial power cannot be used to fill in the blank space. The present project would like to assay the jurisprudence of Regional Federal Court of the 5th Region, pretending to extract the criteria used to attribute tax liability in order to propose a new legislation regarding the theme.